Notes on the parables of our Lord ; v. 2 - Trench, Richard Chenevix, 1807-1886 (London, UK? Kegan, Paul, Trench. Trubne and co?, 1841)
Includes bibliographical references.
Details are unclear. Front cover, tp, etc. missing. Details gleaned from internet sites.
Keywords: Bible. N.T. Parables -- commentaries